Harnessing plant secondary metabolites for vaccine development in Africa: Current insights and future prospects - Chandipwisa, Courage; Banda, Harrison; Shimilimo, Agness (Sciences of Phytochemistry, 2026)
Plant secondary metabolites are natural compounds with immunomodulatory and adjuvant properties that may complement conventional vaccines and support regionally relevant vaccine strategies in Africa. This structured narrative review analyzed English-language studies published between 2000 and 2025 from PubMed, Google Scholar, Elsevier, and EBSCOhost. Included publications comprised original research, systematic reviews, and clinical trials addressing mechanisms, formulation, safety, and clinical development. Evidence included in vitro studies, animal models, formulation research, and human investigations. Preclinical findings show that selected metabolites enhance antigen presentation, promote dendritic cell maturation, and strengthen humoral and cellular immune responses through modulation of key signaling pathways. Triterpenoid saponins from Quillaja saponaria have progressed into clinical adjuvant platforms, while polysaccharides from Moringa oleifera and flavonoids from Curcuma longa and Artemisia annua demonstrate immunostimulatory effects and improved antigen stability in preclinical models. Nanoencapsulation improves compound stability and delivery but lacks sufficient clinical validation. Clinical translation requires standardized phytochemical characterization, comprehensive safety evaluation, regulatory harmonization, validated manufacturing processes, and adequately powered clinical trials with defined immunological endpoints.